Agency costs in primary dealer systems - Filippo Silano (University of Hamburg, Institute of Law and Economics (ILE), 2023)
Easing their access to capital markets, governments have been establishing a primary dealer system. Via bilateral self-enforcing agreements ('dealerships'), government debt management units (DMUs) have been appointing national and global banks (the 'dealers') to actively participate in government securities auctions and/or enhance liquidity in the secondary market. The partnership's non-binding and long-run nature makes dealerships relational contracts. Developing a theoretical framework, this study examines the DMU-dealer principal-agent relationship, with the overarching purpose of identifying and mitigating agency costs. Apart from monitoring costs, the article argues that the partnership entails institutional room for public-private collusion. Although the practice would help fostering the partnership's longevity, it could trigger negative externalities. Mitigating potential risks, policy proposals advocate to enhance: (i) monitoring of the dealers' behaviour in fixed income markets, and (ii) transparency in the DMU's governance of industry's benefits.
Keywords: H63; K12; L14; L51; 330; public finance; government debt management; relational contracts; agency costs; dealers